Upaya Meningkatkan Hasil Belajar IPS Menggunakan Model Pembelajaran CTL (Contextual Teaching and Learning) dengan Media Gambar pada Sdn 6 Selat Hilir Kuala Kapuas Tahun Pelajaran 2016/2017: Efforts to Improve Social Studies Learning Outcomes Using the CTL (Contextual Teaching and Learning) Learning Model with Media Images on Sdn 6 Kuala Kapuas Lower Strait 2016/2017 Academic Year - Lola Selvia; Hendri Hendri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2017)
This study aims to find out: (1) Describe the learning activities of students in social studies subjects using the CTL (Contextual Teaching And Learning) model with picture media. (2) Improving social studies learning outcomes using the CTL (Contextual Teaching and Learning) model with picture media. The type of research used by researchers is Classroom Action Research (CAR). With the subjects in this study were all fifth grade students of SDN 6 in the Lower Strait of Kuala Kapuas, totaling 17 students, 10 men and 7 women. Data collection techniques in this study used a written test at the end of the learning process and observation to find out the activity during the learning process. The data analysis technique uses qualitative and quantitative data analysis. The results of the study showed that: (1) Learning activities of students in social studies learning using the CTL (Contextual Teaching and Learning) model in class V of SDN 6 in the Lower Kapat Kuala Kapuas became good. In the first cycle, the activities of the students obtained a score of 36 with an average rating of 2.57 with quite good criteria. In Cycle II the activities of students received an average score of 53.5 with an average score of 3.82 with suitable measures. (2) There is an increase in learning outcomes of students in social studies learning using the CTL model (Contextual Teaching and Learning) in the fifth grade of SDN 6 in the Lower Straits of Kuala Kapuas. In the pre-test, it can be seen that the percentage of the results is 23.53% (4 people), the students who complete and the students who do not complete 70.48% (12 people) with an average value of 50. The results obtained in the first cycle are the percentage results learners reach 70.59% (12 people) students complete and 23.53% (5 people) students who do not complete with an average value of 72. In cycle II, the acquisition of student learning outcomes is 100% (17 people) who complete with an average score of 91. There is an increase in social studies learning outcomes from pre-test to cycle I which is as much as 47.06% while from cycle I to cycle II there is an increase in learning outcomes which is as much as 29.41%. It can be concluded that there is an increase in learning outcomes by using the CTL (Contextual Teaching and Learning) model in the fifth grade of SDN 6 in the Lower Strait of Kuala Kapuas.